Enzyme response of traumatized tissue after intracortical injection into 5 day old rat brain. Issue 6 (December 1972) - Robinson, N.
Abstract : Penetration of a microneedle and injection of 4 μl. saline into the neocortex of the 5 day old rat brain produced no changes in behaviour of the rats up to 21 days post-injection. Within 24 hours sections indicated that tissue damage was apparent only at the pia-arachnoid membrane and where fluid was released; elsewhere the needle pathway was identified by the enzyme response. The enzyme histochemistry showed a marked increase in glial cell activity of some phosphatases within 24 hours at the site of injury; the pia-arachnoid and outer limiting membrane also showed abnormally high phosphatase reactions. NADH2 -diaphorase was the only dehydrogenase that was raised in some nerve and glial cells at 24 hours post-injection but other dehydrogenases, mainly LDH and SDH, showed changes at four days post-injection. The phosphatases and 5'-nucleotidase previously showing intense glial cell enzyme reactions appeared to reach peaks of activity at eight days, and at 16 days the onset of scarring was apparent. In the pia-arachnoid enzyme activity increased to 21 days. Some enzymes, particularly AChE and MAO, showed no alterations of note throughout.